Ownership and Sustainability of Bai Intangible Cultural Heritage ICH: A Comparative Analysis of Educational Approaches - Tu, Xuejia; Weng, Fwuyuan (Journal of Ecohumanism, 2024)
Through a literature review of scholarly and non-scholarly but credible literature, this study has explored the intricate relationship between ownership, sustainability, and education in the context of the Bai ethnic group’s Intangible Cultural Heritage (ICH) in northwestern Yunnan, China. The Bai people have diverse ICH. However, as China’s ethnic minority, they face challenges from China’s dominant culture and globalization. Therefore, it is critical to sustain their ICH. The review has indicated that the issue of ownership is complex and multifaceted. In most authors have refrain from addressing it. However, there is evidence indicating creating awareness surrounding the ownership of IC can result in social-economic benefits. Such benefits are likely to motivate stakeholders to preserve and certain the. To create awareness and resulting sense of ownership and sustainability, educational approaches, combining formal and informal methods are recommended. So far, this approach exists but they need to be improved further.